Algal biomass and pigments along a latitudinal gradient in Victoria Land lakes, East Antarctica - Borghini, Francesca; Colacevich, Andrea; Caruso, Tancredi; Bargagli, Roberto (Polar Research, 2016)
It is generally accepted that Antarctic terrestrial diversity decreases as latitude increases, but latitudinal patterns of several organisms are not always as clear as expected. The Victoria Land region is rich in lakes and ponds and spans 8 degrees of latitude that encompasses gradients in factors such as solar radiation, temperature, ice cover and day length. An understanding of the links between latitudinally driven environmental and biodiversity changes is essential to the understanding of the ecology and evolution of Antarctic biota and the formulation of hypotheses about likely future changes in biodiversity. As several studies have demonstrated that photosynthetic pigments are an excellent, although underused, tool for the study of lacustrine algal communities, the aim of the present study was to investigate variations in algal biomass and biodiversity across the latitudinal gradient of Victoria Land using sedimentary pigments. We test the hypothesis that the biodiversity of freshwater environments decreases as latitude increases. On the basis of our results, we propose using the number of sedimentary pigments as a proxy for algal diversity and the sum of chlorophyll a and bacteriochlorophyll a with their degradation derivatives as an index of biomass. Overall, our data show that biomass and diversity decrease as latitude increases but local environmental conditions, in particular, natural levels of eutrophy, can affect both productivity and diversity. Keywords: Biodiversity; photosynthetic pigments; proxy; continental Antarctica; sediments; biogeography.
Keywords: Antarktis; alger; biodiversitet; biogeografi; biomasse; ferskvann; fotosyntese; innsjø; sedimenter; økologi

Microbial biogeography during austral summer 2007 in the surface waters around the South Shetland Islands, Antarctica - Olsen, Lasse Mork; Ardelan, Murat van; Hewes, Christopher D; Holm-Hansen, Osmund; Reiss, Christian; Bizsel, Nihayet; Sakshaug, Egil; Vadstein, Olav (Aquatic Microbial Ecology, 2013)
Recent studies have concluded that different water bodies in the ocean can contain different microbial communities. The goal of the present study was to determine if biogeographic patterns are present for aquatic microbes in waters which meet around the South Shetland Islands(SSI), Antarctica. Prokaryotic and eukaryotic marine microbial communities were monitored during the 2007 austral summer by use of polymerase chain reaction (PCR) and denaturing gradientgel electrophoresis (DGGE) of small subunit ribosomal DNA. Hydrographic properties, nutrients and chlorophyll a were also measured. There was an onshore to offshore gradient in temperature, salinity and iron concentration and a unimodal distribution of chlorophyll a concentration in rela-tion to the middle of this gradient that occurred near the SSI. The differences in microbial community structure among stations in the studied area were correlated with both geographical distance and environmental factors. For eukaryotes, the correlation was strongest for environment, where as it was strongest for geographical distance for the prokaryotes. Eukaryotic and prokaryotic community structures were highly correlated. Surface water from the Weddell Sea had a different community of eukaryotes than the water in the Antarctic Circumpolar Current in the Drake Passage, whereas the prokaryotic community was not significantly different. The area close to theSSI where the 2 water types mix had the highest chlorophyll concentration and significantly dif-ferent communities of eukaryotes and prokaryotes from both of the inflowing water types. These results suggest that the prokaryote community structure was more affected by productivity thanby environmental variables. KEY WORDS: Microbial biogeography. Microbial community. Natural iron enrichment. Southern Ocean.
Keywords: Sørishavet; biogeografi; marin biologi; mikroorganismer; oseanografi; overflatevann; økosystemer

Environmental forcings of Paleogene Southern Ocean dinoflagellate biogeography - Bijl, Peter K; Pross, Jörg; Warnaar, Jeroen; Stickley, Catherine E; Huber, Matthew; Guerstein, Raquel; Houben, Alexander J P; Sluijs, Appy; Visscher, Henk; Brinkhuis, Henk (Paleoceanography, 2011)
Despite warm polar climates and low meridional temperature gradients, a number of different high-latitude plankton assemblages were, to varying extents, dominated by endemic species during most of the Paleogene. To better understand the evolution of Paleogene plankton endemism in the high southern latitudes, we investigate the spatiotemporal distribution of the fossil remains of dinoflagellates, i.e., organic-walled cysts (dinocysts), and their response to changes in regional sea surface temperature (SST). We show that Paleocene and early Eocene (∼65–50 Ma) Southern Ocean dinocyst assemblages were largely cosmopolitan in nature but that a distinct switch from cosmopolitan-dominated to endemic-dominated assemblages (the so-called “transantarctic flora”) occurred around the early-middle Eocene boundary (∼50 Ma). The spatial distribution and relative abundance patterns of this transantarctic flora correspond well with surface water circulation patterns as reconstructed through general circulation model experiments throughout the Eocene. We quantitatively compare dinocyst assemblages with previously published TEX86–based SST reconstructions through the early and middle Eocene from a key locality in the southwest Pacific Ocean, ODP Leg 189 Site 1172 on the East Tasman Plateau. We conclude that the middle Eocene onset of the proliferation of the transantarctic flora is not linearly correlated with regional SST records and that only after the transantarctic flora became fully established later in the middle Eocene, possibly triggered by large-scale changes in surface-ocean nutrient availability, were abundances of endemic dinocysts modulated by regional SST variations.
Keywords: Sørishavet; biogeografi; fossiler; paleobotanikk; paleoseanografi; plankton